Screening of a Plant Extract Library from the Greek Flora for Biological Activities Related to Anti-Aging Applications - Harris Pratsinis; Despoina D. Gianniou; Gabriela Belén Lemus Ringele; Adamantia Agalou; Asimina Fotopoulou; Xanthippi P. Louka; Christos Nastos; Eleftherios Kalpoutzakis; Aikaterini Argyropoulou; Dimitris Michailidis; Antonia Theodoridi; Ioanna Eleftheriadou; et al. (Antioxidants)
Characteristic manifestations of skin aging, due to either intrinsic or extrinsic factors, such as ultraviolet (UV) radiation and oxidative stress, include cell senescence, alterations in collagen and elastin networks, and melanogenesis disorders. Natural products are considered a rich source of anti-aging molecules. Accordingly, the screening of a plant extract library from the Greek flora for a panel of biological activities related to skin aging is presented herein. In particular, 52 plant materials extracted using Accelerated Solvent Extraction (ASE) and Supercritical Fluid Extraction (SFE) were assessed for their effects on (1) human skin cell viability, (2) antioxidant activity—using both cell-free and cell-based methods—(3) photoprotective capacity, and (4) interference with collagenase, elastase, and tyrosinase, as well as with proteasomal and lysosomal activities of human skin cells. In vivo phenotypic screens on Danio rerio (zebrafish) embryos were also used for assessing melanogenesis. Many active extracts were identified, some of them for the first time, and others in agreement with previous reports. In general, ASE extracts exhibited higher activities than SFE ones. Seven extracts showed multiple activities, being highly effective in at least four different assays. These data support the potential use of these extracts against skin aging in medicinal and cosmetic applications.